Pemanfaatan Media Sosial Instagram Sebagai Media Promosi Kesehatan Untuk Meningkatkan Efektivitas Pelayanan Kesehatan Ibu Dan Anak Di Puskesmas X - Laeli Malida Dela Sabila; Wahyuni Arumsari; Dwi Nur Siti Marchamah (Universitas Ivet, 2025)
Health Center X, one of the health centers that, in its health promotion activities for maternal and child health services in Semarang City, uses the Instagram social media. In a preliminary study, it was found that no data or evaluation showed how effective the use of Instagram was in improving the achievement of maternal and child health services. The study aimed to determine the relationship between the use of Instagram social media as a health promotion medium to improve the effectiveness of maternal and child health services at Health Center X. This type of research was quantitative with a cross-sectional approach. Data analysis used chi-square. The results of the study stated that the variable of the use of Instagram social media as a promotional medium was that 57% of respondents stated it was good. The variable of the effectiveness of maternal and child health services that 54% of respondents stated it was effective. There was a relationship between the use of Instagram social media as a promotional medium and the effectiveness of maternal and child health services at Health Center X because the p-value <0.001. Suggestions for conducting periodic monitoring evaluations to determine the effectiveness of health promotion and services.